2017
DOI: 10.1177/0308518x17727284
|View full text |Cite
|
Sign up to set email alerts
|

The legitimization of concern: A flexible framework for investigating the enactment of stakeholders in environmental planning and governance processes

Abstract: From the 1990s and onwards, environmental planning and governance has undergone a broad participatory turn. This paper focuses on one specific aspect of participatory processes and the concrete arrangements through which they are carried out, more specifically: how such processes always come to enact some actors as ‘legitimately concerned’ stakeholders and others not. Such investigations bring into focus context-specific effects of inclusion and exclusion as well as de/legitimization of specific actors and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…We argue that the framings provided by the regulatory process itself may exercise an influence that renders such recommendations less effective than might be expected. Our research questions align with those identified by Metzger, Soneryd, and Linke (2017), who ask for an emphasis not on who the legitimate stakeholders in planning are, but rather on the processes by which they get defined. We similarly ask how local actors in NSIPs are framed and what are the implications for regulatory decision-making?…”
mentioning
confidence: 84%
“…We argue that the framings provided by the regulatory process itself may exercise an influence that renders such recommendations less effective than might be expected. Our research questions align with those identified by Metzger, Soneryd, and Linke (2017), who ask for an emphasis not on who the legitimate stakeholders in planning are, but rather on the processes by which they get defined. We similarly ask how local actors in NSIPs are framed and what are the implications for regulatory decision-making?…”
mentioning
confidence: 84%
“…Admittedly, ambiguities such as these are partly why procedural theorists insist on the need for “some ideal against which to compare its performance” (Webler, 1995: 38). But regardless of the merits of such ideals, as shown above, they nonetheless risk obscuring the “unpurposeful infrastructures” (Metzger et al, 2017), which always organize participatory arrangements into a practice with “fundamentally unpredictable outcomes” (Turnhout et al, 2010: 37). In line with previous agnostic approaches to the study of participation, these outcomes frame participatory governance as a complex ensemble of arrangements that can be “both enabling and restricting at the same time” (Braun and Schultz, 2010: 404).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…In this article, I argue that these debates have tended to neglect actual legitimacy demands and what determines them in favor of broadly abstract, theoretical-normative understandings of democratic legitimacy which foreground if it is engendered or not, but rarely how, in what forms, and by whom. In line with recent calls for more normatively agnostic and measured approaches to the study of participatory governance (Braun and Schultz, 2010; Metzger et al, 2017; Turnhout et al, 2010), my overarching aim is to bring attention to how strong normative assumptions regarding the inherent democratic merits of participation conceal many of the complex motivations, expectations, and experiences these arrangements produce among citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Presenting almost fully formed plans as one-way flow of information-or consultation-is also seen as a lower order and perhaps even undermining form of participation that can work to undermine the legitimacy of public governance initiatives like MSP by exacerbating power differences and elitism. As Metzger et al (2017) and others have noted, who frames what a stakeholder is in planning or 'stakeholderness' (conferring in MSP 'the property of being considered legitimately concerned', p. 2) will affect how and what stakeholders are represented and included. If the preponderance of MSP's strategic focus is on Blue Growth and/or environmental protection, there is little likelihood that social sustainability (and associated 'stakes') will be seen as a legitimate concern without some form of explicit representation and/or constitutive reform of MSP.…”
Section: Deeping Democratic Decision-making In Mspmentioning
confidence: 99%